Self-confidence due to ability of Three Meter Smash in Volleyball - Purnomo, Arif; Hariono, Awan (Universitas Nusantara PGRI Kediri, 2020)
This research aimed at determining the athlete's level of confidence in the three-meter smash on volleyball. The research method used was descriptive quantitative. The instrument used was questionnaire about athlete’s confidence with 20 questions. The subject of the research were 12 volleyball extracurricular athletes in SMA Negeri 1 Pundong, Bantul. The data technique analysis used were validity measured by using the Product Moment Correlation formula and reliability gained 0.428 using Cronbach's Alpha. The result of the research showed that the level of confidence of volleyball athletes in SMA Negeri 1 Pundong while conducting a three meter smash was in the category: Very low, 5 persons (41.6%); Low, 3 persons (25%); High, 2 persons (16.7%); Very high, 2 persons (16.7%). The ability to smash three meters can only be done by especially in the open spiker and all-round. It is needed to support their ability in doing the three-meter smash. This study is limited with a few research subjects for those who specialize in open spikes and all rounds who usually do three meter semash. More research subjects with open and all-round specialties were reproduced.